2020
DOI: 10.1177/1060028020944596
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Review of Biosimilars Approved in Oncology

Abstract: Objective: To summarize and review the clinical data of Food and Drug Administration (FDA)-approved biosimilars for use in treatment of cancer and the current challenges health care institutions face when implementing a newly approved biosimilar. Data Sources: A literature search of the following databases was performed between January 1, 2012, and December 31, 2019: PubMed, Google, and ClinicalTrials.gov. Search terms included the words biosimilar, bevacizumab, rituximab, and/or trastuzumab. Study Selection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…As of November 2020, there are two FDA-approved rituximab biosimilars that were licensed in the USA under section 351(k) of the Public Health Service Act. Clinical trials demonstrated equivalent pharmacokinetics, as well as comparable safety and efficacy, for rituximab biosimilars in FL [12]. Two rituximab biosimilars (rituximab-abbs [Truxima R ] and rituximab-pvvr [Ruxience R ]) received FDA approval for all the approved oncology indications of the rituximab reference medication, including those utilizing monotherapy and combination therapies [13,14].…”
mentioning
confidence: 99%
“…As of November 2020, there are two FDA-approved rituximab biosimilars that were licensed in the USA under section 351(k) of the Public Health Service Act. Clinical trials demonstrated equivalent pharmacokinetics, as well as comparable safety and efficacy, for rituximab biosimilars in FL [12]. Two rituximab biosimilars (rituximab-abbs [Truxima R ] and rituximab-pvvr [Ruxience R ]) received FDA approval for all the approved oncology indications of the rituximab reference medication, including those utilizing monotherapy and combination therapies [13,14].…”
mentioning
confidence: 99%
“…13 However, current literature consists mainly of Phase III clinical trials published by manufacturers of the biosimilar product where conflicts of interest may exist. 12 A 2019 systematic review and metaanalysis by Lee et al 14 involved both rheumatoid arthritis patients and NHL patients; however, more evidence has emerged since then which is specifically relevant to the oncology setting. [15][16][17][18][19][20][21]…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence suggests no statistically significant difference in efficacy and safety between biosimilars and their reference biologics 13 . However, current literature consists mainly of Phase III clinical trials published by manufacturers of the biosimilar product where conflicts of interest may exist 12 . A 2019 systematic review and meta‐analysis by Lee et al 14 .…”
Section: Introductionmentioning
confidence: 99%
“…This consideration will be especially important for biologic medical products that are heavily used in SOC regimens, eg, bevacizumab, rituximab, and trastuzumab. 1 These scenarios will require additional time, money, and other resources from site research staff, eg, clinical research coordinators and investigational drug pharmacists, and should be factored into consideration when discussing budgeting and contracts between the site and the sponsor.…”
mentioning
confidence: 99%
“…Because they are proteins with complex three-dimensional structures manufactured using eukaryotic cell machinery, even identical biological products can exhibit some variability. 1 In the United States, the FDA currently approaches biosimilar approval with a totality of evidence approach, whereas new biologic approval requires extensive clinical data. To maximize the cost benefits of biosimilar development and uptake, the FDA has shifted the focus of commercialization of a biosimilar on randomized clinical trials to emphasize comparative analytical, preclinical, and pharmacological data more heavily than clinical data.…”
mentioning
confidence: 99%